Adult Learning in Online Educative Spaces: A Constructive-Developmental Perspective - Alexandra Cox (Adult Education Research Conference, 2017)
This study explored how adults construct meaning, develop, and grow within the particular context of a structured, online, educative space and through the alone/together paradox.
Keywords: online learning; adult development; alone/together paradox